The 24th annual meeting of the European Tissue Repair Society (ETRS) in Edinburgh, Scotland. Issue 6 (November 2014) - Shaw, Tanya J.; Lippens, Evi
Abstract From the 10th to 12th of September 2014, in the midst of the Scottish Independence debate, the European Tissue Repair Society descended on Edinburgh for their 24th Annual Meeting. In the beautiful and historic setting of the Royal College of Surgeons of Scotland, Professors David Thomas (Chair), Phil Stephens, Chris Lloyd, and their teams from Cardiff hosted an educational and inspiring program.